2006
DOI: 10.1080/20786204.2006.10873436
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' perceptions of their development of ‘soft skills’ Part II: The development of ‘soft skills’ through ‘guiding and growing

Abstract: BackgroundThis paper reports on medical students' views on the ways in which their 'soft skills' were developed. It is the result of a study on soft skills among two groups of students before and after curriculum reform at the School of Medicine of the University of Pretoria. One of the aims of the reform was to provide more teaching and learning opportunities for the development of soft skills. Soft skills include professional interpersonal and social skills, communication skills, and professional and ethical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 21 publications
5
26
0
2
Order By: Relevance
“…Normative competence or soft skills, according to Bergh et al. , are considered to include ‘interpersonal and social skills in a caring, professional doctor–patient relationship, communication skills and professional and ethical attitudes'. Lowther et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normative competence or soft skills, according to Bergh et al. , are considered to include ‘interpersonal and social skills in a caring, professional doctor–patient relationship, communication skills and professional and ethical attitudes'. Lowther et al.…”
Section: Introductionmentioning
confidence: 99%
“…Normative competence or soft skills, according to Bergh et al (2), are considered to include 'interpersonal and social skills in a caring, professional doctor-patient relationship, communication skills and professional and ethical attitudes'. Lowther et al (4) refer to these skills, or what they termed as 'normative capabilities', as those skills that are generic and which describe the manner in which technical skills are delivered.…”
Section: Introductionmentioning
confidence: 99%
“…The perceptions relating to the environment in which experiential learning takes place were very similar. (du Preez et al 2005;Bergh et al 2006) Students' perceptions of role models and the experiential learning environment as reflected in their more recent assignments on professionalism seem to indicate that although the cognitive component of the curriculum has improved, a renewed effort needs to be made to improve teaching and assessment of the development of professionalism in the experiential component of the curriculum.…”
Section: Teaching Professionalism E289mentioning
confidence: 99%
“…They found capability to work getting better when there is integration between technical skills and soft skills. Similarly, research on the advantage of integrated of soft skills learning found the development of soft skills through guiding and growing [17]. They found integration soft skills into curriculum give variation on learning experiences, especially when interacting with students [17].…”
Section: ) Problem Solving A)mentioning
confidence: 99%
“…Similarly, research on the advantage of integrated of soft skills learning found the development of soft skills through guiding and growing [17]. They found integration soft skills into curriculum give variation on learning experiences, especially when interacting with students [17]. Learning activities that created by lecturer assist students in developing and constructing soft skills independently.…”
Section: ) Problem Solving A)mentioning
confidence: 99%